ELECTRON MICROSCOPY OF POLYRIBOSOMES WITHIN BACILLUS CEREUS - Pfister, R. M. (1964)
Pfister, R. M. (Syracuse University, Syracuse, N.Y.), and D. G. Lundgren. Electron microscopy of polyribosomes within Bacillus cereus. J. Bacteriol. 88:1119–1129. 1964.—Clusters of ribosomes (polyribosomes) were identified in thin sections of Bacillus cereus. Cells were treated by freezing and thawing to induce partial lysis to permit a closer examination of structural detail. The polyribosomes were (at times) attached to the cytoplasmic membrane, and ribosome clusters contained about 10 to 55 individual ribosomes. Individual ribosomes ranged from 70 to 100 A, whereas polyribosomes were about 150 to 850 A wide. A membrane served as the fabric holding the ribosomes, which were about 50 to 100 A apart.